Seeking control: Disentangling the difficult sociality of Kakadu National Park's joint management. (June 2013) - Haynes, Chris
This article discusses joint management in Kakadu National Park, Australia's biggest and arguably most complex protected area, where the policy is devised to allow sharing of power between the state and the area's traditional Aboriginal owners. Although power is shared, this happens in a clumsy and difficult-to-understand way, confusing a divided group of actors. Most of them are convinced that most power lies with the other group and that they themselves are powerless to deal with contesting forms of cultural capital. In arguing this position I show how structure and habitus have become entrenched in one domain of the park's management but radically changed in another.